Effects of Soils on the Holocene History of Forest Communities, Cape Cod, Massachusetts, U.S.A. - Tzedakis, P. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1992)
ABSTRACTPalynological evidence from a sediment sequence in Owl Pond, Cape Cod, Massachusetts, documents the persistence of an area of oak-white pine dominated vegetation through most of the Holocene. The small size of the basin (1.6 ha) and its small catchment area suggest that it receives most pollen from nearby vegetation and consequently its pollen record can be used to study the history of the surrounding forests. The 10,500-year pollen record showed three main phases of relative vegetational stability. A late-glacial spruce-jack pine forest phase, followed by an early Holocene phase when white pine dominated the landscape while oak and pitch pine became increasingly important. After 9000 yr BP, an oak-dominated forest was established. White pine continued to be an important component of the forest. This pattern is similar to vegetational changes elsewhere in southern New England, except for the relatively high values of pine pollen, which reflect the influence of the sandy glacial soils on Cape Cod. The pollen record from Owl Pond is compared with that from another site on Cape Cod, Duck Pond. Oak pollen values are higher at Owl Pond, but values of pitch pine pollen are higher at Duck Pond for the past 8000 years. Soil type (composition, texture) is judged to be the most important factor in maintaining the differences between the two sites. The results from Owl Pond suggest that mainly through the local control of the substrate, a mosaic of oak-dominated patches of vegetation existed at places on Cape Cod during the Holocene, interspersed within a pitch pine-dominated landscape.